Social Media use among Indonesiaâ€™s Generation Z: A Case of University Students in Bandung, West Java - Gandana, Isti; Oktaviandy, Rivaldya (KOMUNITAS: International Journal of Indonesian Society and Culture, 2021)
Globalization cannot be detached from the processes and results of global interconnections. As one of the most remarkable products of globalization, the internet appears to have become an important part of many peopleÃ¢â‚¬â„¢s lives. Among the youth, social media is of particular prominence. This study explores the engagement of a group of Indonesian university students aged 20 to 23Ã¢â‚¬â€also known as the Generation ZÃ¢â‚¬â€in using social media. The study specifically attempted to inquire into ways in which they perceive social media to impact their lives. Ã‚Â Questionnaire and individual interviews were used as data collection techniques. Analysis of the data pointed to a high degree of Ã¢â‚¬ËœaddictionÃ¢â‚¬â„¢ to social media use among students in general.Ã‚Â  The students also revealed both positive and negative impacts of social media use, thus confirming the idea that social media is a double-edged sword that needs to be dealt with carefully and critically.